Prognostic value of albumin-based malnutritional indices on short-term outcome in acute ischemic stroke patients undergoing reperfusion therapy - Zhao, Junle; Chen, Mingjie; Mo, Junning; Zhong, Yutong; Qiu, Jiamin; Qiu, Yanjiao; Li, Youjia; Han, Xiaoyan (Frontiers in Nutrition, 2025)
BackgroundThe malnutrition and inflammatory status are dependently associated with an increased risk of poor prognosis in patients with acute ischemic stroke (AIS). However, the evidence surrounding the prognostic significance of albumin-based malnutritional indices in AIS patients receiving reperfusion therapy remains insufficient. We aimed to explore prognostic value of the controlling nutritional status score (CONUT), prognostic nutritional index score (PNI), and neutrophil percentage-to-albumin ratio (NPAR) on short-term outcome of AIS patients undergoing reperfusion therapy.MethodsA total of 612 AIS patients were enrolled. The association of the malnutritional indices and 3-months poor prognosis was accessed by multivariable logistics regression model. We further performed a logistic regression model with restricted cubic splines to examine the potential nonlinear correlations between the malnutritional indices and short-term poor prognosis. Subgroup analysis and reclassification indexes were also conducted to enhance the robustness of the findings. Additionally, mediation analyses were performed to examined the potential mediating effects of early neurological deterioration (END) presence on the associations of malnutrition with 3-months unfavorable outcomes.Results256 patients developed poor prognosis at 3-month follow-up. Malnutrition was associated with the risk of 3-month poor functional outcome for CONUT (per 1-point increased, adjusted OR 1.59, 95%CI 1.40–1.82), for PNI (per 1-point increased, adjusted OR 0.86, 95%CI 0.82–0.90), and the NPAR (per 1-SD increased, adjusted OR 23.97, 95%CI 7.15–85.72). The PNI exhibited nonlinear association with the 3-month poor prognosis. These three indices in addition to other clinical risk factors improved the model discrimination. Compared to the NPAR, the net reclassification improvement of PNI (0.579, 95%CI 0.418–0.739) and CONUT (0.631, 95%CI 0.470–0.792) were higher in predicting short-term poor prognosis. The findings were further supported by subgroup analyses, and END had no significant mediated effects on the associations of malnutrition and 3-month unfavorable outcome.ConclusionAlbumin-based malnutritional indices are reliable and feasible prognostic indicators in AIS patients, predicting short-term outcome independent of the type of reperfusion treatment. The applicability of these objective malnutritional indices may improve risk stratification and guide nutritional interventions at clinical setting in this vulnerable ischemic stroke population.